Description using ultramorphological techniques of the infection of Beauveria bassiana (Bals.-Criv.) Vuill. in larvae and adults of Atta sexdens (Linnaeus, 1758) (Hymenoptera: Formicidae) - Travaglini, Raphael Vacchi; Forti, Luiz Carlos; Arnosti, Andre; Stefanelli, Luis Eduardo Pontes; Ferreira, Allan Roberto Fernandes; Camargo, Roberto da Silva; Camargo-Mathias, Maria Izabel (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2020)
Leaf-cutting ants, whose name comes from the habit of cutting leaves and other parts of plants, are dominant herbivores in the Americas, attacking different crops to keep symbiotic fungi (their main food source) in the colony. These ants are soil inhabitants, an environment rich in microorganisms, many of which are considered entomopathogenic. In order to describe a kind of microbial biological control of these ants through histological techniques, we used the fungus Beauveria bassiana (Bals.- Criv.) Vuill. Larvae and adult workers of Atta sexdens (Linnaeus, 1758) were exposed to a fungal suspension with the concentration of 106/conidia/mL. The specimens were adequately prepared to describe the behavior of the fungus on the integument at 24, 48 and 72 hours after initial exposure. Some specimens were used to represent these periods, being properly processed for scanning electron microscopy, which was applied to document the fungus development on the surface of the insect integument. To better understand the dynamics of the fungal infection, from the conidial adhesion to the potential colonization of the insides of the insect, the histological technique with HE staining was applied. The results showed that, in immature individuals, the hyphal penetration of B. bassiana fungi into the insect integument occurred in 48 h.
Keywords: Leaf-cutter ants; Immature; Biological control; Entomopathogenic fungi